Studi Deskriptif Mengenai Job Demand dan Job Resources pada Karyawan Junks Radio Kota Bandung - Lulu Syadza Syahzan; Lisa Widawati (Bandung Conference Series: Psychology Science, 2022)
Abstract. Every modern organizations want employees who have work engagement. In the JD-R model there are job demand and job resources which are being the predictor of work engagement on employees. However, not all of the developing companies take notice to the balance of job demand and job resources for their employees. Radio is one of creative industries that are potentials in Bandung where the balance of of job demand and job resources is needed in order to continue to grow in modern era. In this research it is seen to how job demand and job resources from 24 employees of Junks Radio who have engagement within their work. This research uses quantitative approach and descriptive study method using the JDRS scale (Job Demand-Resource Scale) Jackson & Rothmann (2005) which had been adaptated by the previous researcher. The result of this study using SPSS-25 calculation shows that on Junks Radio employees have high job demand (78,8%) and high job resources (95,8%) so according to the JDRS interpretation it is found that Junks Radio employees see their job as a challenging work. Abstrak. Setiap organisasi modern menginginkan karyawan yang memiliki work engagement. Dalam model JD-R terdapat job demand dan job resources yang menjadi prediktor adanya work engagement pada karyawan. Namun tidak semua perusahaan berkembang memperhatikan keseimbangan dari beban kerja dan sumber daya bagi karyawan. Radio merupakan salah satu jenis dari industri kreatif yang potensial di Kota Bandung dimana dibutuhkan keseimbangan job demand dan job resources yang tersedia guna terus mampu berkembang di era modern. Pada penelitian ini dilihat job demand dan job resources dari 24 karyawan Junks Radio yang memiliki ikatan dengan pekerjaannya. Penelitian menggunakan pendekatan kuantitatif dan metode studi deskriptif dengan menggunakan alat ukur JDRS (Job Demand-Resource Scale) Jackson & Rothmann (2005) yang telah diadaptasi dari peneliti sebelumnya. Hasil penelitian menggunakan pergitungan SPSS-25 menunjukkan bahwa pada karyawan Junks Radio Job demand tinggi (78,8%) dan job resources tinggi (95,8%) sehingga berdasarkan interpretasi JDRS didapat bahwa karyawan Junks Radio mempersepsikan pekerjaan sebagai pekerjaan yang menantang.